United States Marine Corps aircraft since 1913 - Johnson, E. R., 1948- (McFarland & Company, Inc., Publishers, 2018)
"Among the world's military air arms, United States Marine Corps Aviation occupies a tactical niche. This comprehensive survey provides the history, technical specifications, drawings, and photographs of every type of fixed and rotary-wing aircraft used by Marine Air from its origins prior to World War I up to current operations"--